2002
DOI: 10.1097/00006454-200204000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rapid polymerase chain reaction results on management of pediatric patients with enteroviral meningitis

Abstract: Rapid reporting of PCR results can have a significant impact on several outcome measures for patients with EV meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 13 publications
3
93
2
2
Order By: Relevance
“…The analysis comparing clinical data for patients whose positive EV-PCR results were available within 24 hr and those whose results were available >24 hr after CSF collection showed a positive correlation between the TAT and the duration of antibiotic treatment. However, as observed previously [Robinson et al, 2002], there was no statistically significant difference in the length of stay. A comparison of the clinical data of patients admitted over the weekend and of those admitted during the week showed that the length of stay was one day shorter (P ¼ 0.02) and the use of antibiotics lower when EV-PCR was performed daily.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The analysis comparing clinical data for patients whose positive EV-PCR results were available within 24 hr and those whose results were available >24 hr after CSF collection showed a positive correlation between the TAT and the duration of antibiotic treatment. However, as observed previously [Robinson et al, 2002], there was no statistically significant difference in the length of stay. A comparison of the clinical data of patients admitted over the weekend and of those admitted during the week showed that the length of stay was one day shorter (P ¼ 0.02) and the use of antibiotics lower when EV-PCR was performed daily.…”
Section: Discussionsupporting
confidence: 79%
“…This assay is an effective alternative to viral culture, since it can provide rapid results within 5-24 hr of receipt of the sample [Ramers et al, 2000;Stellrecht et al, 2002;Archimbaud et al, 2004]. Previous studies of children suggested that the use of the enterovirus PCR assay has a clinical benefit by reducing antibiotic or antiviral therapy, and avoiding ancillary tests, and also it reduces hospital related costs allowing earlier discharge [Hamilton et al, 1999;Ramers et al, 2000;Robinson et al, 2002;Stellrecht et al, 2002]. Children are the primary victims of enterovirus meningitis, but the illness is not uncommon in adults [Rotbart et al, 1998;Peigue-Lafeuille et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Enteroviruses are the most common cause of aseptic meningitis in both children and adults and may cause up to 90% of cases of aseptic meningitis for which an etiology is identified (1,14,18,19). The rapid detection and the rapid characterization of enteroviral meningitis are essential for making decisions for patient management and treatment (5,15,17,20). The provision of enterovirus test results on a daily basis can have a substantial impact on health care and has been shown to be highly cost-effective (9,12,17).…”
mentioning
confidence: 99%
“…Several other groups have analyzed the clinical impact of real-time PCR testing for CSF enterovirus. Projected direct variable cost savings were achieved by earlier discharge of patients and decreased use of antibiotics, [11][12][13] although some of the cost reductions depend on the prevalence of enterovirus meningitis exceeding a certain threshold. 13 In conclusion, we developed a real-time PCR for HSV using the Cepheid SmartCycler with sensitivity comparable to that of national reference laboratories using LightCycler.…”
Section: Discussionmentioning
confidence: 99%